Implementation of The Concept of Tazkiyat Al-Nafs Imam Al-Ghazali in The Cultivation Of Student Moral Education at The Al-Aly Bojonegoro Modern Islamic Boarding School - Anwar, Saeful; Fikri, Ahmad Dianul; Izza, Yogi Prana (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2025)
This research reveals the importance of purifying the soul (tazkiyatun nafs) of the santri, which is realized in daily praiseworthy morality. The response that needs to be made by the world of education is to re-examine the formulation of moral education in teaching and learning in order to produce knowledgeable students who are able to utilize the knowledge they have learned. The implementation of Tazkiyat Nafs, in character building, is realized through a morally based curriculum, exemplary teachers, self-introspection programs, spiritual efforts, disciplinary training, and extracurricular activities. The purpose of the research is the application of Imam Ghazali's tazkiyat nafs in the moral development of Pondok Modern Al-Aly Bojonegoro students, as well as integration in the curriculum and akhlaq development program. The research uses qualitative methods through observation, interviews, and document analysis. The results showed that Imam Ghazali developed tazkiyat nafs through self-cleansing from despicable traits and replacing them with praiseworthy habits. The application of this concept through the stages of muhasabah, mujahadah, and riyadah is effective in the moral education of students, although there are inhibiting and supporting factors that arise. It is hoped that the research will have an impact on the implementation of applied learning.